Between Freedom and Justice: Popular Protest and Jurisdictional Contestation of Militarized Governance in Indian-Controlled Kashmir. (October 2020) - Hoffman, Bruce; Duschinski, Haley
In Indian-controlled Kashmir, local residents express aspirations for freedom from Indian-militarized governance even as they demand state accountability for pervasive everyday violence. Kashmiris negotiate this complexity through jurisdictional contestation, asserting alternative forms of authority to speak about law and develop strategies for justice and political transformation. Drawing from sociolegal literatures of jurisdiction and global legal pluralism, we analyze a Kashmiri community forum confronting institutional denial in a prominent case of sexual violence and murder involving state armed forces. We analyze how Kashmiri actors from diverse normative communities drew on popular understandings of law to claim competing forms of authority, give meaning to the case, and develop strategies of response. We also explore how participants, through the work of jurisdictional contestation, made global legal ideas locally meaningful and relied on jurisdictional myths of struggle and justice to motivate resistance and establish spaces of hope.